Strength recovery and healing efficiency of cement-based materials containing autogenous healing binders and autonomous encapsulated healing agents - Mohammed, Abdulmohaimen Imad (2021)
Self-healing is a new technology that is about promoting the recovery of mechanical properties of concrete without any external aid, to reduce maintenance costs. However, previous studies have reported some issues related to the encapsulation of healing agent, as capsules are unable to survive mixing process, or may slip without breaking due to their low bonding strength. Moreover, it was reported that autogenous healing has very limited ability in term of healable crack widths, while autonomous healing had an issue where capsules may not break and release the healing agent. Even more, it was reported that MgO expansive agent may cause strength reduction to concrete, which is disadvantageous. Therefore, this study aims to propose new surface modifications to polystyrene capsules; smooth, rough and weakness lines cylindrical sphere polystyrene capsules, that helps to enhance their ability to survive mixing process without being damaged, and with high bonding strength. In addition to that, this study is suggesting an enhancement to the autogenous and autonomous healing systems by including silica fume. Also, an investigation and comparison to the healing and sealing performance of autogenous, autonomous and a combination of both systems is conducted, together with an assessment to the healing compounds developed on the microstructure level for each healing system. In this study, there are four mix combinations consists of OPC, silica fume and MgO expansive agent, with three variables which are smooth, rough and weakness lines capsules to carry sodium silicate (Na2SiO3) healing agent. The scope of work focuses on two main issues; (i) study of mineral admixtures in autogenous self-healing, and (ii) study the potential improvement to the encapsulation method used for autonomous self-healing. For the first issue, the evaluation was based on; (i) the healing ability of cement compounds by expansive admixture only, and (ii) the healing ability of cement compounds by a combination of mineral and expansive admixtures. Whereas the second issue focuses on; (i) capsule modification, (ii) evaluation of healing ability of cement compounds by encapsulated sodium silicate only, and (iii) evaluation of healing ability of cement compounds by a combination between encapsulated method and mineral admixtures. The evaluation of capsules was conducted based on their compressive strength, bonding strength, mixing survivability and the ability to survive elevated temperatures. Whereas for self-healing assessment, specimens were divided into two sets; the first set was left un-cracked, while the second set of specimens were pre-cracked after 7 days of water immersing curing using two different pre-cracking methods; the first method used for cubes by applying 80% of ultimate compressive strength, while the second method used for prisms by bending using 3-points flexural. Thereafter, specimens of both sets were re-immersed in water for further curing durations of 28, 56, 90 and 120 days. The healing and sealing performance of cement paste, mortar and concrete were assessed based on; the compressive and flexural strength regain, and crack sealing based on crack depth and area. Thereafter, microstructure assessment was conducted to determine the healing compounds developed on the crack planes using SEM and FTIR tests. Moreover, statistical analysis using ANOVA and multiple linear regression (MLR) were conducted to evaluate the effect of using silica fume, the difference in performance of each healing mechanism and to formulate prediction equations for strength recovery. In conclusion, this research confirmed the efficiency of the new encapsulation surface modifications in term of mixing survivability and bonding strength, which was reflected on the self-healing performance. In addition to that, silica fume was proved to be able to successfully enhance the autogenous healing, and the combined self-healing system was proved to be superior in comparison to both autogenous and autonomous self-healing systems in term of strength recovery and crack sealing performance.